2015
DOI: 10.3892/ijmm.2015.2253
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective effects of a recombinant protein from Pyropia yezoensis and synthetic peptide against acetaminophen-induced Chang liver cell death

Abstract: In the present study, the chemoprotective effects of recombinant Pyropia yezoensis (P. yezoensis) protein 1 (PYP1) were examined in acetaminophen (APAP)-treated Chang liver cells. The analysis of P. yezoensis revealed the presence of both mature and immature variants of PYP1. PYP1s, designated as PYP1 (15 kDa), PYP1-AC (12 kDa) and PYP1-B (5 kDa), were successfully expressed in Escherichia coli, and their chemoprotective effects were then examined. In addition, a peptide of 11 residues (ALEGGKSSGGG), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Many studies have explored the functional effects of peptides from P. yezoensis , which has exhibited enhanced cell viability by reducing ER stress induced via environmental pollutants [ 28 ]. It also had the ability to decrease oxidative stress caused by hydrogen peroxide and acetaminophen in Chang cells [ 21 , 23 , 24 ]. A recent study also demonstrated that a P. yezoensis peptide attenuated muscle atrophy in murine C2C12 myoblasts [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have explored the functional effects of peptides from P. yezoensis , which has exhibited enhanced cell viability by reducing ER stress induced via environmental pollutants [ 28 ]. It also had the ability to decrease oxidative stress caused by hydrogen peroxide and acetaminophen in Chang cells [ 21 , 23 , 24 ]. A recent study also demonstrated that a P. yezoensis peptide attenuated muscle atrophy in murine C2C12 myoblasts [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A red alga, Pyropia yezoensis ( P. yezoensis ), is widely cultured as food and as a nutritional supplement for its biofunctional components such as proteins, vitamins, minerals, and mycosporine-like amino acids [ 21 , 22 ]. Moreover, peptides or glycoproteins derived from P. yezoensis protect against oxidative stress induced by acetaminophen or hydrogen peroxide in Chang and human hepatoblastoma HepG2 cells [ 23 , 24 ], and promote cell proliferation in intestinal epithelial IEC-6 cells via the activation of phosphatidylinositol 3-kinase (PI3K)-Akt signaling [ 25 ]. A recent study also demonstrated that a peptide derived from P. yezoensis (PYP) regulated muscle atrophy by inhibiting atrogin1/muscle atrophy F-box (MAFbx) and muscle RING Finger 1 (MuRF1) signaling in mouse myoblast C2C12 cells [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. yezoensis -derived peptides are known to exert various biological effects, including antioxidant [11], antitumor [12], and anti-inflammatory activities [13]. Previous studies have reported that peptides synthesized from P. yezoensis reduced the inflammatory stress induced by lipopolysaccharides in RAW 264.7 cells, and cytotoxicity induced by acetaminophen in Chang cells [13,14]. Moreover, P. yezoensis peptides prevented the endoplasmic reticulum stress induced by perfluorooctane sulfonate in Chang cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, P. yezoensis peptide (PYP) is known to have antioxidant and chemoprotective properties (11,12). However, the bioactivity of PYP in ER stress conditions induced by environmental pollutants has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%